2017
DOI: 10.3847/2041-8213/aa67f8
|View full text |Cite
|
Sign up to set email alerts
|

Active Cryovolcanism on Europa?

Abstract: Evidence for plumes of water on Europa has previously been found using the Hubble Space Telescope (HST) using two different observing techniques. Roth et al. (2014) found line emission from the dissociation products of water. Sparks et al. (2016) found evidence for offlimb continuum absorption as Europa transited Jupiter. Here, we present a new transit observation of Europa that shows a second event at the same location as a previous plume candidate from Sparks et al. (2016), raising the possibility of a consi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
136
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 37 publications
6
136
0
Order By: Relevance
“…However, it is interesting that the area associated with the Galileo nighttime thermal excess is actually colder in the ALMA data than the model predicts. For the Galileo PPR observation, shown in Figure 2 alongside the best-fit model image and the resulting residuals, the same location is indeed anomalously warm, as noted by Spencer et al (1999) and Sparks et al (2017). In fact, the entire Pwyll Crater region, not just the potential plume source location slightly northwest of the crater, shows up as anomalously hot at night and cold during the day.…”
Section: Fits To Alma and Galileo Ppr Observationsmentioning
confidence: 81%
See 4 more Smart Citations
“…However, it is interesting that the area associated with the Galileo nighttime thermal excess is actually colder in the ALMA data than the model predicts. For the Galileo PPR observation, shown in Figure 2 alongside the best-fit model image and the resulting residuals, the same location is indeed anomalously warm, as noted by Spencer et al (1999) and Sparks et al (2017). In fact, the entire Pwyll Crater region, not just the potential plume source location slightly northwest of the crater, shows up as anomalously hot at night and cold during the day.…”
Section: Fits To Alma and Galileo Ppr Observationsmentioning
confidence: 81%
“…An elevated thermal inertia near Pwyll Crater and the anomaly in question, as originally noted by Spencer et al (1999), may result from higher average regolith particle sizes in the ejecta blanket. This possibility seems particularly plausible as the anomalous temperatures are not just constrained to the relatively small potential plume source area (Sparks et al 2017), but are observed across the entirety of the Pwyll region (Figures 1 and 2). Spencer et al (1999) also suggest the possibility that impact-exposed water ice may allow for deeper sunlight penetration, which, as discussed in Section 3, can mimic the effects of increased thermal inertia.…”
Section: Fits To Alma and Galileo Ppr Observationsmentioning
confidence: 99%
See 3 more Smart Citations